2022
DOI: 10.3390/vaccines10010076
|View full text |Cite
|
Sign up to set email alerts
|

Influences on Pregnant Women’s and Health Care Professionals’ Behaviour Regarding Maternal Vaccinations: A Qualitative Interview Study

Abstract: The uptake of maternal influenza and pertussis vaccinations is often suboptimal. This study explores the factors influencing pregnant women’s and health care professionals’ (HCPs) behaviour regarding maternal vaccinations (MVs). Pregnant/recently pregnant women, midwives, pharmacists and general practice staff in Waikato, New Zealand, were interviewed. The analysis used the behaviour change wheel model. Interviews of 18 women and 35 HCPs revealed knowledge about MVs varied with knowledge deficiencies hindering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 47 publications
1
40
1
Order By: Relevance
“…Our qualitative research component of this project found multiple barriers to maternal vaccination uptake [21]. The provision of funded maternal vaccinations in pharmacy can help address awareness, provide information, aid opportunistic vaccination, and reduce barriers to access, such as requiring an appointment, Monday to Friday availability only in general practices, and a concern about sitting in a waiting room with sick people.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our qualitative research component of this project found multiple barriers to maternal vaccination uptake [21]. The provision of funded maternal vaccinations in pharmacy can help address awareness, provide information, aid opportunistic vaccination, and reduce barriers to access, such as requiring an appointment, Monday to Friday availability only in general practices, and a concern about sitting in a waiting room with sick people.…”
Section: Discussionmentioning
confidence: 99%
“…While ideally maternal vaccinations would be available from multiple locations, and particularly from antenatal care providers who could administer them during the antenatal appointment, this might not be practical for all antenatal care providers. For example, in NZ, barriers to midwives providing maternal vaccinations include challenges of administering a vaccine then being called urgently elsewhere, travelling to women's homes and maintaining cold chain, or purchasing a vaccine fridge and not being funded for this service [21]. Many midwives in NZ work alone or in a partnership, and may visit the woman at home, rather than working in a hospital or larger birthing centre where vaccinations may work better logistically.…”
Section: Comparison With Other Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The other factor that significantly reduced influenza vaccine uptake in univariate and multivariate analysis was delivering in a midwife-lead setting. Recommendations from healthcare professionals play a key role in encouraging vaccination during pregnancy [37] , with women often valuing the recommendations and convictions of midwives over that of other health professionals [38] . However, a Canadian survey found that recommendations for influenza vaccination during pregnancy vary among healthcare members, with midwives (38%) being less likely than physicians (80%) to recommend the influenza vaccine to their patients [39] .…”
Section: Discussionmentioning
confidence: 99%
“…Trusting midwives recommendations is a known factor to support vaccine uptake [ 13 ]. However, the reasons that pregnant women remain unimmunised are often complex and multifactorial [ 14 , 15 ]. Some women may not receive adequate information about recommended vaccinations during pregnancy [ 14 ], particularly if they live in areas of high deprivation [ 16 ], resulting in lack of awareness in these groups that vaccinations are recommended during pregnancy [ 14 ].…”
Section: Introductionmentioning
confidence: 99%